Hyperoside exerts anti-inflammatory and anti-arthritic effects in LPS-stimulated human fibroblast-like synoviocytes in vitro and in mice with collagen-induced arthritis - Jin Xiang-nan; Yan En-zhi; Wang Han-ming; Sui Hai-juan; Liu Zhou; Gao Wei; Jin Ying (Acta Pharmacologica Sinica, 2017)
Aim: Hyperoside is a flavonol glycoside mainly found in plants of the genera Hypericum and Crataegus, which has shown anti-oxidant, anti-cancer and anti-inflammatory activities. In this study, we investigated the effects of hyperoside on human rheumatoid fibroblast-like synoviocytes (FLSs) in vitro and on mouse collagen-induced arthritis (CIA) in vivo. Methods: FLSs were isolated from primary synovial tissues obtained from rheumatoid arthritis (RA) patients and exposed to LPS (1 μg/mL). Cell viability and proliferation were measured with MTT and BrdU assay. Cell migration was assessed using wound-healing assay and Transwell assay. DNA binding of NF-κB was measured using a TransAM-NFkappaB kit. The localization of p65 subunit was detected with immunocytochemistry. CIA was induced in mice by primary immunization with Bovine Type II collagen (CII) emulsified in CFA, followed by a booster injection 3 weeks later. The arthritic mice were treated with hyperoside (25, 50 mg·kg−1·d−1, ip) for 3 weeks, and the joint tissues were harvested for histological analysis. Results: Hyperoside (10, 50, 100 μmol/L) dose-dependently inhibited LPS-induced proliferation and migration of human RA FLSs in vitro. Furthermore, hyperoside decreased LPS-stimulated production of TNF-α, IL-6, IL-1 and MMP-9 in the cells. Moreover, hyperoside inhibited LPS-induced phosphorylation of p65 and IκBα, and suppressed LPS-induced nuclear translocation of p65 and DNA biding of NF-κB in the cells. Three-week administration of hyperoside significantly decreased the clinical scores, and alleviated synovial hyperplasia, inflammatory cell infiltration and cartilage damage in mice with CIA. Conclusion: Hyperoside inhibits LPS-induced proliferation, migration and inflammatory responses in human RA FLSs in vitro by suppressing activation of the NF-κB signaling pathway, which contributes to the therapeutic effects observed in mice with CIA.